ENTREPRENEURSHIP AS A FACTOR OF ECONOMIC DEVELOPMENT: FEATURES OF MANIFESTATION IN FORESTRY - Sakal, Oksana; Третяк, Наталія; Штогрин , Галина; Бегаль, Іван (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article presents the results of the study the essence and features of entrepreneurship manifestation in forestry in terms of assessing the realities and prospects of its development in Ukraine. For this purpose, it is studied general principles of doing business (entrepreneurship) in Ukraine, legal norms that determine the general features of entrepreneurship in this area. Based on the multifunctionality of forests, it is substantiated that entrepreneurial activity in forestry has a deeper ecological, economic and social meaning, compared to other areas of activity. It is noted that the dual nature of forest resources causes the diversification of types and organizational forms of entrepreneurship throughout the forest sector. Extended reproduction in the research area according to the concept of sustainable development has an impact on the well-being of more than one generation. This factor becomes decisive in the latest economic conditions and determines the adoption of appropriate measures of economic stimulation of the intensive type of economic growth of expanded forest production. The results of the analysis of the activities of forestry enterprises, corporate interests of forestry activities, as well as the role of the state and environmental insurance are the basis for determining the prospects for long- and short-term temporary use of forests in Ukraine. It is noted that the development of the study field of economy of Ukraine, in conjunction with measures of financial and economic incentives wood industry can contribute to the development of the last one. The study on the example of forestry allowed us to generalize that the entrepreneurial vector of nature using is to organize and support business activities of nature users, in their relations with other economic entities of various forms of ownership, with the state under existing and exacerbating environmental restrictions. and burdens, taking into account the ecological and social functions and services of ecosystems.